Manajemen Warung Rakyat Pintar Berbasis Teknologi Informasi - Luna Adhani Putri; Darius Antoni (Jurnal Nasional Ilmu Komputer, 2021)
This study aims to help the people's stalls in improving the people's warung system into smart stalls using a technology system that is now growing rapidly, it is necessary to have a technology-based smart warung concept by managing the stalls using 4 indicators in management, namely planning, organizing, implementing. , and supervision. The research method that the author uses in this study is a qualitative method, with a case study approach. Techniques for determining the data in this study include: Observation, interviews, and documentation. Based on the results of the research obtained, the system designed for smart stalls is the POS (Point Of Sale) application system, and the internet network smart shop. The design of the technology system in the smart shop contains several simple design features to manage small businesses to medium retail businesses. The system is designed and designed for use on smartphones and tablets based on android. The system for smart stalls is designed as a cash register software to help business owners easily manage various types of businesses and shops.